Liquidity risk in economic uncertainty: Evidence from Indonesian Islamic banks - Muhammad Anis; Baitul Hamdi (Jurnal Ekonomi & Keuangan Islam, 2022)
Purpose – This paper aims to analyze the effect of economic uncertainty on liquidity risk of Islamic banks in Indonesia by observing the impact of economic uncertainty (World Uncertainty Index), macroeconomic factors (GDP Growth and Inflation Rate), and bank-specific factors (CAR and ROA) on liquidity risk.Methodology – Using time-series quarterly data from OJK’s Islamic Banking Statistics 2015-2021, this research applies Auto-Regressive Distributed Lag (ARDL) and Error Correction Term (ECT) to see the long-term impact and short-term response of economic uncertainty, inflation rate, GDP growth, ROA and CAR on liquidity risk of Islamic Bank.Findings – This research finds that economic uncertainty has a positive and significant effect on liquidity risk in the short term and long term. It means the increase in uncertainty index caused by the crisis, war, or pandemic like nowadays will enhance the liquidity risk of Islamic banking. At the same time, the inflation rate has a significant negative effect on liquidity risk in the short-term and long term.Originality – This research uses a combination of macroeconomic variables and bank-specific factors, and the economic uncertainty variable from the World Uncertainty Index. In this case, one of the reasons for liquidity problems apart from fund management failure is unfavorable economic conditions. In addition, this study also provides several recommendations in maintaining banking liquidity risk.Research limitations – This study uses time-series data with a limited period (2015Q1-2021Q2). In addition, this uses cumulative data on Islamic banking in Indonesia; thus, it does not describe the conditions in each Islamic bank, although certainly there are some different conditions between each other. Therefore, it is hoped that studies will complement these limitations in the future.